Health care professionals' self-assessed competence in empowering patient education - Pernica, Katrin (My University, 2021)
Background: Patient empowerment is becoming increasingly important as constantly changing health services make patients increasingly responsible for their own health and self-care. Although patient education is a key nursing intervention, which has proven to be an effective method of promoting patients' empowerment, limited evidence is available about health care professionals' competence in empowering patient education. This study provided the first self-assessment of competence in empowering patient education. Purpose: The purpose of this study was to analyze health care professionals' self-assessed competence in empowering patient education and associated factors. Methods: A comparative descriptive design was used. Data were collected in October and November 2019 from 473 health care professionals of one hospital in Finland (N = 1110 / response rate 42.6 %) using the Competence in Empowering Patient Education Instrument (CompEPE© Virtanen, Hupli, Leino-Kilpi 2019). The instrument consists of 84 items measuring knowledge and skills concerning the method and specific content areas of empowering patient education. Competence was measured using a visual analog scale (VAS) with 'low competence = 0' on one end and 'high competence = 10' on the other end. Descriptive and inferential analyses were con-ducted using SPSS 25.0. Results: Health care professionals assessed their overall competence as well as competence in method and content of empowering patient education at a good level. In relation to the method, they assessed their competence in implementation of empowering educational methods slightly higher than the identification of the patient’s existing resources as a starting point and the evaluation of empowering educational outcomes as an end point of the discourse. Competence related to the content they assessed highest on the biophysiological and lowest on the economic subscale. Confidence in patient education, age and work experience in health care were statistically significantly related to health care professionals' self-assessed competence. Conclusion: Health care professionals assessed their competence in empowering patient education on a good level. The method competence related to the implementation of empowering educational methods was rated highest. The content focused mostly on biophysiological and least on economic issues. Confidence in patient education was one of the more significant background factors associated with the self-assessed competence in empowering patient education. Part of the master's thesis has been reported as a separate scientific article.

Johdanto: Potilaan voimavaraistumisen merkitys kasvaa, koska nopeasti muuttuvien terveyspalveluiden myötä potilas on yhä enemmän vastuussa omasta terveydestään ja sen hoitamisesta. Potilaan ohjaus on hoitotyön keskeinen toiminto, jolla voidaan tukea ja edistää potilaan voimavaraistumista. Tarkoitus: Tutkimuksen tarkoituksena oli kuvata hoitotyön ammattilaisten voimavaraistumista tukevaa ohjausosaamista heidän itsensä arvioimana sekä tunnistaa ohjausosaamisen tasoon vaikuttavia tekijöitä. Menetelmät: Tutkimus toteutettiin kuvailevana kyselytutkimuksena yhdessä sairaalassa Etelä-Suomessa. Yhteensä 473 mukaanottokriteerit täyttäneistä hoitotyön ammattilaisista (N = 1110) palauttivat täytetyn kyselylomakkeen (vastausprosentti 42.6 %). Aineistokeruumenetelmänä käytettiin Voimavaraistumista tukevan ohjauksen osaaminen – kyselylomaketta (CompEPE© Virtanen, Hupli, Leino-Kilpi 2019). Kyselylomakkeen sisältämät 84 väittämää mittasivat hoitotyön ammattilaisten tietoa ja taitoa, jotka liittyvät potilaan voimavaraistuvan ohjauksen menetelmälliseen ja sisällölliseen osaamiseen. Ohjausosaamisen tasoa arvioitiin visuaalisella analogiasteikolla (VAS) nollasta (= Osaan erittäin huonosti) kymmeneen (= Osaan erittäin hyvin). Aineistoa analysoitiin tilastollisin menetelmin. Tulokset: Keskimäärin tutkimukseen osallistujat olivat 44-vuotiaita (kh 11.5) ja heillä oli 17.4 vuotta (kh 11.0) työkokemusta terveydenhuollossa. He arvioivat ohjausosaamisensa kokonaisuudessaan hyvälle tasolle. Voimavaraistumista tukevien ohjausmenetelmien toteuttaminen osana menetelmällistä ohjausosaamista arvioitiin hieman korkeammaksi aloitus- ja lopetusvaiheeseen verrattuna. Sisällöllistä ohjausosaamista arvioitiin korkeimmin biofysiologisella ja alhaisimmin taloudellisella osa-alueella. Luottavaisuus omaan ohjausosaamiseen, ikä ja työkokemus terveydenhuollossa olivat tilastollisesti merkitsevästi yhteydessä itsearvioituun ohjausosaamiseen. Johtopäätökset: Hoitotyöntekijät arvioivat ohjausosaamisensa hyvälle tasolle. Menetelmällisestä ohjausosaamisesta arvioitiin ohjauskeskustelun eteneminen korkeimmaksi. Potilaan ohjauksen sisältö osattiin parhaiten biofysiologisella ja vähiten taloudellisella osa-alueella. Luottavaisuus omaan ohjausosaamiseen oli yksi tilastollisesti merkittävimmistä taustatekijöistä, jotka olivat yhteydessä voimavaraistumista tukevan ohjauksen osaamiseen. Osa pro gradu -tutkielmasta on raportoitu erillisenä tieteellisenä artikkelina.
Keywords: patient education, competence, empowering discourse, patient empowerment